The effect of massage education on low birth weight (LBW) babies on the stimulation of their growth and development - Hariana Erdewi Sinaga (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Low Birth Weight (LBW) babies are babies weighing less than 2,500 grams at birth and are at high risk for health problems and developmental delays. One intervention that can be provided is infant massage education as a form of early stimulation to promote growth and development. However, the application of infant massage to LBW babies is still not optimal in independent midwifery practices. Purpose: to determine the effect of massage education on LBW babies on stimulating infant growth and development. Method: This study used a quantitative approach with a quasi-experimental design (nonequivalent control group design). The sample consisted of all 14 low birth weight (LBW) infants registered in the Jayusnijar PMB register. Data collection was conducted through the stages of midwifery care, including assessment, diagnosis, planning, implementation, and evaluation. Data analysis used the nonparametric Wilcoxon Signed Rank Test to assess the effect of baby massage on infant growth and development. Results: The majority of respondents were female (64.3%), second-born (57.1%), and born by cesarean section (78.6%). After the intervention, 7 babies (50.0%) in the control group experienced optimal improvement, while 12 babies (85.7%) in the experimental group experienced optimal improvement. The statistical test results showed a significant effect of baby massage on stimulating infant growth and development with a p-value of 0.021 (p < 0.05). Conclusion: Education and baby massage significantly influence the growth and development of LBW infants. This intervention can be recommended as part of midwifery care to improve the growth quality of LBW infants.